The Internal Competency Model Of The Auditor At The Cimanuk Cisanggarung Cirebon Center Focuses On Enhancing The Performance Of Internal Auditors. - Risdianto, Risdianto; Suprihatin, Dina; Nurhawaeny, Endah (Jurnal Ekuisci, 2024)
Implementing a competency model in firms might yield advantages in enhancing the management system. This study seeks to ascertain the impact of the internal competency model on financial accounting auditors at the Cimanuk Cisanggarung Cirebon Center. This study investigates the impact of internal auditor competency on the performance of internal auditors. This research is a form of quantitative descriptive research that examines the impact of an auditor's internal competence on their internal performance. The indicators employed in this study encompass quality, quantity, timeliness, effectiveness, independence, and organizational commitment. The study findings indicate that competence has a notable and positive impact on the internal performance of auditors.